PENGARUH PEMASANGAN SIRIP PENGARAH PADA BUFFER TERHADAP UNJUK KERJA MOTOR BENSIN - Muh Nurkoyim Kustanto (ROTOR, 2011)
Perfect combustion can improve engine performance and save fuel consumption. One of the requirements perfect combustion is a homogeneous mixture of fuel and air when entering the combustion chamber. Air and fuel mixture to become homogeneous in case of turbulence in the mixing. Buffer with director fin is used to provide additional mixing time between air and fuel at the same time create a turbulent flow before entering the combustion chamber. In this study the buffer fitted with director fins with different variations. The number of fins variation used in this study are 3, 4, 6, 8 and 10 with a variation of the angle are 45o and 60o. The analysis was conducted on the effective power and torque output and the FC (Fuel Consumption) needed from each variation condition buffer. From the results of testing on the condition of the buffer with 3 fins angled 60o obtain the highest effective power increase 5.92% and increase in the highest torque 2.66% when compared with the buffer without fins. The lowest FC (Fuel Consumption) in the buffer with 3 fin angle 60 ° when compared with the buffer without any fins at 4000 rpm with a 11.15% difference. Keywords: homogeneous, turbulent, buffer and fin